IMPLEMENTASI PROGRAM PENDAMPINGAN KADER JUMANTIK DALAM RANGKA PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI PERUMAHAN TAMAN PERMATA REGENCY, JERUKSAWIT - Bara Yudhistira; Arianto Agus Prasetyo; Ananta Bhirawa Putra Nugroho; Ardha Pamilutama; Ayik Nurmalita Setyati; Cantika Aurellia Azarine; Citra Putri Nur Yuwono; Dafa Fadhilah; Damarati Bestari; Karina Aurellia Putri Murti; Melviana Mayandra Putri Budi Setyo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health challenge in Indonesia, especially in densely populated urban areas such as the Taman Permata Regency Housing Complex in Jeruksawit. This study aims to assess the effectiveness of the Juru Pemantau Jentik (Jumantik) cadre assistance program in improving the technical capacity and performance of cadres while encouraging community participation in DHF prevention efforts. The community service method was carried out through socialization, briefings, and practical monitoring of mosquito larvae with the distribution of monitoring cards and abate powder as a short-term chemical intervention. The results showed a significant increase in the technical ability of cadres in detecting and monitoring Aedes aegypti mosquito breeding sites, supported by collaborative synergy between student assistants, cadres, and the community. Although the cadres' knowledge increased, the challenges of community behavior resistance and the lack of a structured documentation system became major obstacles to the sustainability of the program. This study recommends strengthening behavioral education, digitizing reporting, and establishing formal partnerships with health agencies to ensure the continuity and effectiveness of this community empowerment program. These findings provide an important contribution to the development of an adaptive and sustainable dengue prevention model at the urban community level.